Die grosse Edgar Wallace Krimi-Collection - Wallace, Edgar 1875-1932 (The Edgar Wallace Mysteries, 2024)
Edgar Wallace (1959) Alan Roper is a smart young man on the fringes of big time crime. With his partner-in-crime, Lea, and his girlfriend Pat, he's planning his biggest job yet - the robbery of a betting shop owned by a man he hates. [www.imdb.de]